2017
DOI: 10.1016/j.clnu.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrition on somatotropic axis: Milk consumption in adult individuals with moderate-severe obesity

Abstract: A novel positive association between milk consumption, GH status, and metabolic profile in obese individuals was evidenced. Regardless of the pathogenetic mechanisms, this novel association might be relevant in a context where commonly obese individuals skip breakfast, and suggests the need of a growing cooperation between Nutritionists and Endocrinologists in the management of the obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…The anthropometric assessment was performed following standard criteria by the same nutritionist. The subjects were recommended to dress in light clothes and to remove shoes during the assessment [15][16][17]. The BMI (weight (kg) divided by height squared (m 2 ), kg/m 2 ) was calculated after measuring weight and height.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anthropometric assessment was performed following standard criteria by the same nutritionist. The subjects were recommended to dress in light clothes and to remove shoes during the assessment [15][16][17]. The BMI (weight (kg) divided by height squared (m 2 ), kg/m 2 ) was calculated after measuring weight and height.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…The BIA phase-sensitive system (800 µA, 50 kHz; BIA 101 RJL, Akern Bioresearch, Florence, Italy) was used by experienced observers to assess body composition [19] as previously reported [17,[20][21][22]. We performed the exam as suggested by the European Society of Parental and Enteral Nutrition (ESPEN) [23].…”
Section: Bioelectrical Impedance Analysismentioning
confidence: 99%
“…The anthropometric measurements were performed following standard criteria from the same nutritionist according to the International Society for the Advancement of Kinanthropometry (ISAK 2006). The subjects were recommended to dress in light clothes and remove shoes during the assessment, as previously reported [32][33][34][35].…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…A wide variety of studies have revealed that dairy products bring a positive impact for many pathologies like obesity, hypertension, type 2 diabetes, cardiovascular diseases, metabolic syndrome and cancer. Furthermore, the consumption of dairy foods enhances bone health [2][3][4][5][6][7][8]. In addition to that, yogurts constitute a privileged vehicle for administration of live microorganisms known as probiotics, which have demonstrated positive health benefits for the host [9].…”
Section: Introductionmentioning
confidence: 99%